2021
DOI: 10.1017/s0144686x2100091x
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of driven-game shooting as a psycho-social resource for older adults in rural areas: a mixed-methods study

Abstract: This paper explores whether regular involvement in a rural, country sport, frequently practised by older individuals, builds social capital and friendships, reduces loneliness, and positively impacts individuals’ health and wellbeing. Taking a critical realist, mixed-methods approach, using a recognised social impact assessment methodology theoretically underpinned by social capital theory, this study identifies that driven-game shooting participation creates social impact via social capital creation and ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 54 publications
(88 reference statements)
0
8
0
Order By: Relevance
“…For older adults in rural areas, expansion of social networks is achieved through participation in physical and social activities ( 68 ). These activities include participating in sports ( 31 ), community events and meetings ( 54 ). De Koning et al ( 33 ) noted that physical activity can play role in developing new social contacts.…”
Section: Theme 1 Development Of Social Network For Older Adults In Ru...mentioning
confidence: 99%
See 3 more Smart Citations
“…For older adults in rural areas, expansion of social networks is achieved through participation in physical and social activities ( 68 ). These activities include participating in sports ( 31 ), community events and meetings ( 54 ). De Koning et al ( 33 ) noted that physical activity can play role in developing new social contacts.…”
Section: Theme 1 Development Of Social Network For Older Adults In Ru...mentioning
confidence: 99%
“…The review identified a variety of interventions to address loneliness among older people, based on their differing purpose, underlying mechanisms for action and expected outcomes. The purpose of the interventions included: increasing physical activity and social connectedness of older adults ( 68 ), enhancing social participation ( 89 , 90 ), building social capital and friendship ( 31 ), mediating loneliness and perceived stress among older people ( 91 ), enhancing connectedness, informal care giving and local participation ( 73 ), improving general mental health, nutritional status, satisfaction with life, and social capital ( 92 ) tackling social isolation and loneliness ( 58 , 93 95 ).…”
Section: Theme 3 Interventions To Address Loneliness Among Older Adul...mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, González-Bernal et al (2021), from a pretest/post-test design study, investigated the impact of using the Wii video game console ® on speed, walking balance, and risk of falls in older adults. Likewise, Santamaría-Guzmán et al (2015), address the learning and motor retention of a video game in older adults, which demanded a lot of mobility from the point of view of dance; Along these same lines, Corregidor- Sánchez et al (2021) analyze the usefulness of exergames played on three different video game consoles for the prevention of functional deterioration in the elderly; taking into account the rural context, Latham-Green et al (2021), identify that participation in shooting games creates a social impact through the creation of social capital and the reinforcement of identity, which, according to the authors, generates a statistically significant positive impact on mental health and well-being ; likewise, Li et al (2020) structured a video game that combines cognitive and physical training in a virtual reality environment, demonstrating how a multitasking game, based on virtual reality, can have a positive impact on the physical and cognitive health of the elderly.…”
Section: Introductionmentioning
confidence: 99%